STITCH Analysis, ADMET Profiling, Molecular Docking, DFT, and Molecular Dynamics of Compound from Eleutherine americana L. Merr as Cyclooxygenase-2 Inhibitor - Ayu Faadila; Wiji Utami; Aisyah Aisyah (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2026)
Dayak onion (Eleutherine americana (L.) Merr) is known to have potential as an inflammatory pathway modulator as it contains active compounds such as eleutherine, isoleutherine, and eleutol. They are known to have anti-inflammatory, antioxidant, and anti-cancer activities. This study explored the potential of Eleutherine americana (L.) Merr bioactive compounds as COX-2 enzyme inhibitors using an in silico approach. The data were obtained using Lipinski’s rule of 5, ADMET profile prediction, molecular docking, and molecular dynamics simulation. The molecular docking results showed that eleutherin, isoeleutherin, and elecanacin had strong binding affinities of −8.09, −8.19, and −8.06 kcal/mol to the active site of COX-2 with amino acid residues SER530, ALA527, SER353, HIS90, PHE518, LEU384, and PHE381. Meanwhile, MD analysis showed that eleutherin formed stable RMSD Cα interactions at a distance of 1.4 Å for 100 ns with COX-2, while isoeleutherin showed slight fluctuations of 2.5 Å at 75 ns with an average radius of gyration of 24 Å. The findings demonstrate potential for further development, particularly in the exploration of new herbal-based drug discovery using Eleutherine americana (L.) Merr, and can be studied further in vitro and in vivo to validate the drug candidate as a COX-2 inhibitor in anti-inflammatory therapy.